2020
DOI: 10.1007/s00348-020-03026-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mach number on droplet aerobreakup in shear stripping regime

Abstract: The present experimental study investigates the shear stripping breakup of single droplets in subsonic and supersonic gaseous flows. In contrast to most research that places emphasis on the Weber number (We), we focus on the individual effects exerted by flow Mach (M∞) and Reynolds numbers (Re). Millimeter-sized droplets made of either ethylene glycol or water are exposed to shock-induced flows. Shadowgraph and schlieren images of the breakup process are recorded by an ultra-high-speed camera. The experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 49 publications
6
35
0
Order By: Relevance
“…Overall, the predominant pattern is the further decrease of the secondary droplets' sizes inside the dispersed mist, which is also reflected in the droplet population in Figure 8(i), highlighting an increase and dominance of the smallest scales over time. A distribution of uniformly small-scaled fragments is also demonstrated in the experiments of Wang et al [25] at subsonic postshock flows. In case 2, shown in Figure 9(ii), the creation of smaller-scaled droplets, driven by the local turbulence and collision, remains dominant for the mist evolution with a minor decrease compared to case 1.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Overall, the predominant pattern is the further decrease of the secondary droplets' sizes inside the dispersed mist, which is also reflected in the droplet population in Figure 8(i), highlighting an increase and dominance of the smallest scales over time. A distribution of uniformly small-scaled fragments is also demonstrated in the experiments of Wang et al [25] at subsonic postshock flows. In case 2, shown in Figure 9(ii), the creation of smaller-scaled droplets, driven by the local turbulence and collision, remains dominant for the mist evolution with a minor decrease compared to case 1.…”
Section: Resultssupporting
confidence: 57%
“…During the evolution of aerobreakup, the coalescence region expands, driven by the increasing local flow vorticity. Similarly, in the study of Wang et al [25], the presence of larger fragments among the dominant microdroplets is observed at the advanced stages of aerobreakup under supersonic postshock conditions. As discussed in [25] and in agreement with the present subgrid scale analysis, these nonuniform fragments coalesce into larger secondary droplets, as imposed by the local flow conditions and the limited spanwise spread on the produced dense mist.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations